Pseudomonas aeruginosa L10: A Hydrocarbon-Degrading, Biosurfactant-Producing, and Plant-Growth-Promoting Endophytic Bacterium Isolated From a Reed (Phragmites australis) - Wu, Tao; Xu, Jie; Xie, Wenjun; Yao, Zhigang; Yang, Hongjun; Sun, Chunlong; Li, Xiaobin (Frontiers in Microbiology, 2018)
Bacterial endophytes with the capacity to degrade petroleum hydrocarbons and promote plant growth may facilitate phytoremediation for the removal of petroleum hydrocarbons from contaminated soils. A hydrocarbon-degrading, biosurfactant-producing, and plant-growth-promoting endophytic bacterium, Pseudomonas aeruginosa L10, was isolated from the roots of a reed, Phragmites australis, in the Yellow River Delta, Shandong, China. P. aeruginosa L10 efficiently degraded C10–C26 n-alkanes from diesel oil, as well as common polycyclic aromatic hydrocarbons (PAHs) such as naphthalene, phenanthrene, and pyrene. In addition, P. aeruginosa L10 could produce biosurfactant, which was confirmed by the oil spreading method, and surface tension determination of inocula. Moreover, P. aeruginosa L10 had plant growth-stimulating attributes, including siderophore and indole-3-acetic acid (IAA) release, along with 1-aminocyclopropane-1-carboxylic (ACC) deaminase activity. To explore the mechanisms underlying the phenotypic traits of endophytic P. aeruginosa L10, we sequenced its complete genome. From the genome, we identified genes related to petroleum hydrocarbon degradation, such as putative genes encoding monooxygenase, dioxygenase, alcohol dehydrogenase, and aldehyde dehydrogenase. Genome annotation revealed that P. aeruginosa L10 contained a gene cluster involved in the biosynthesis of rhamnolipids, rhlABRI, which should be responsible for the observed biosurfactant activity. We also identified two clusters of genes involved in the biosynthesis of siderophore (pvcABCD and pchABCDREFG). The genome also harbored tryptophan biosynthetic genes (trpAB, trpDC, trpE, trpF, and trpG) that are responsible for IAA synthesis. Moreover, the genome contained the ACC deaminase gene essential for ACC deaminase activity. This study will facilitate applications of endophytic P. aeruginosa L10 to phytoremediation by advancing the understanding of hydrocarbon degradation, biosurfactant synthesis, and mutualistic interactions between endophytes and host plants.